At the End of a Slippery Slope: A Pilot Study of Deceleration Mats for Snow Tubing - Irving S. Scher (MDPI AG, 2021)
On-slope pilot testing of snow tubes was conducted at two ski areas in the United States to examine the effects of deceleration mats. Snow tube and rider kinematics were measured using an instrumented bodysuit and a GPS system worn by the rider. For each test, the riders descended a tubing run with minimal input and stopped in the run-out area. Snow tube and rider speeds when entering the run-out area were controlled to be approximately 9.5 m/s. Test trials were conducted with and without deceleration mats. Four deceleration mat conditions were tested, including two raised surface protuberances (ribs and projections) and two mat geometry parameters (flat and folded). The deceleration and effective coefficient of friction (COF) were determined for each trial. Data were recorded for 75 test trials with a mean (± standard deviation) speed entering the run-out area of 9.5 (±1.8) m/s. There were no significant differences in the deceleration or effective coefficient of friction between the surface protuberance conditions. The peak deceleration and effective COF for the folded mats (5.1 ± 1.6 m/s2 and 0.26 ± 0.14) was greater than for the flat (3.3 ± 0.8 m/s2 and 0.10 ± 0.07) and no mat (0.06 ± 0.3 m/s2 and 0.08 ± 0.03) conditions (all p < 0.05). Deceleration mats in run-out areas slow snow tube riders faster than without deceleration mats. Folding the deceleration mats produced greater deceleration but did not produce significantly different kinematics for the riders.